Effects of dopants on the biomechanical properties of conducting polymer films on platinum electrodes - Baek,S; Green,RA; Poole-Warren,LA (Journal of Biomedical Materials Research - Part A, 2014)
Conducting polymers have often been described in literature as a coating for metal electrodes which will dampen the mechanical mismatch with neural tissue, encouraging intimate cell interactions. However, there is very limited quantitative analysis of conducting polymer mechanics and the relation to tissue interactions. This article systematically analyses the impact of coating platinum (Pt) electrodes with the conducting polymer poly(ethylene dioxythiophene) (PEDOT) doped with a series of common anions which have been explored for neural interfacing applications. Nanoindentation was used to determine the coating modulus and it was found that the polymer stiffness increased as the size of the dopant ion was increased, with PEDOT doped with polystyrene sulfonate (PSS) having the highest modulus at 3.2 GPa. This was more than double that of the ClO 4 doped PEDOT at 1.3 GPa. Similarly, the electrical properties of these materials were shown to have a size dependent behavior with the smaller anions producing PEDOT films with the highest charge transfer capacity and lowest impedance. Coating stiffness was found to have a negligible effect on in vitro neural cell survival and differentiation, but rather polymer surface morphology, dopant toxicity and mobility is found to have the greatest impact. © 2013 Wiley Periodicals, Inc.